Optimization of an aircraft flight trajectory in the GLONASS dynamic accuracy field - O. N. Skrypnik (Naučnyj Vestnik MGTU GA, 2019)
The authors consider the problem of optimization of aircraft flight trajectories in air traffic management (ATM) on the basis of flexible routing technologies which involve the use of satellite navigation systems (SNS). It is shown that in optimizing a trajectory it is necessary to take into account the accuracy of track holding during the flight which depends on the accuracy of the navigation system and external flight path disturbances, e.g. wind. For solving the task of optimization the authors propose to use the theory of graphs. The technique of constructing a dynamic SNS accuracy field and representing it as a graph was developed. It is proposed that the SNS field be characterized by geometric dilution of precision changing both in space and in time. Based on the theory of graphs (A-star algorithm) the technique of constructing a trajectory of optimal length with changing the SNS accuracy and external flight path disturbances is proposed. The criterion of optimization based on minimizing the true track is offered. The cost function taking into account the track holding accuracy in navigating by SNS and effects of external flight disturbances is justified. The article presents the results of A-star algorithm application for constructing an optimal flight trajectory under conditions of SNS accuracy field variation and presence of prohibited zones in the provided airspace.